Analisis Toxic Masculinity terhadap Perilaku Merokok Remaja Laki-Laki Awal di Wilayah Kerja Puskesmas Ambulu Kabupaten Jember - Ardelia Lingga Nayottama (Fakultas Kesehatan Masyarakat, 2026)
Background: Smoking behavior among early adolescent boys remains a persistent public health challenge in Indonesia, including Jember Regency. While smoking is often studied through individual and peer lenses, the sociocultural construction of masculinity, particularly toxic masculinity, heavily shapes this behavior. This study aims to analyze the influence of toxic masculinity aspects specifically dominance and greed on the smoking behavior of early adolescent boys. Method: This study employed a descriptive qualitative approach with a phenomenological design. Data were gathered between January and March 2026 through in-depth interviews and documentation in the service area of the UPTD Ambulu Community Health Center (Puskesmas), Jember Regency. Informants were selected via purposive sampling, consisting of 7 active early adolescent boy smokers in junior high school and 2 peers as supporting informants. Data analysis was conducted using thematic content analysis based on a modified Antecedent-Behavior-Consequence (ABC) framework. Results: The antecedent of dominance manifests as adolescents use smoking to establish leadership, influence, and social control over peer groups, treating cigarettes as symbols of courage and power. The antecedent of greed operates through a heightened drive for social recognition, popularity, and material status, evidenced by behaviors like performing smoke tricks and chasing premium cigarette brands to assert superiority. Smoking intensity falls into the light smoker category (2–3 cigarettes daily), predominantly triggered after meals and during peer socialization. Functionally, smoking serves to mitigate physical withdrawal symptoms (mouth numbness) and regulate emotions to achieve psychological tranquility. Conclusion: Smoking behavior among early adolescent boys is intrinsically tied to the social construction of unhealthy masculine identities rather than being a mere individual habit. Dominance and greed drive the initiation and maintenance of smoking as validation mechanisms. Interventions must move beyond conventional health risks and focus on dismantling toxic gender norms to cultivate healthier conceptions of masculinity.
FINALISASI oleh Arif 2026 Agustus 11
Keywords: Toxic Masculinity; Smoking Behaviour